Runoff sensitivity to climate and land-use changes: A case study in the Longtan basin, Southwestern China - Guiyan Mo (IWA Publishing, 2021)
Based on the scenario hypothesis method, this paper applied a Soil and Water Assessment Tool (SWAT) to analyze the sensitivity of runoff to climate and land-use changes in the Longtan basin, China. Results indicated that (1) for every 1 °C increase in temperature, the average annual runoff decreased by 9.9 mm, and the average annual evaporation increased by 9.3 mm. However, for every 10% increase in rainfall, the average annual runoff and evapotranspiration increased by 96.3 mm and 11.53 mm, respectively. Obviously, runoff was more sensitive to the change in rainfall than temperature in the Longtan basin. Meanwhile, (2) forestland could conserve water resources, but its water consumption was larger. Although grassland played a relatively small role in water conservation, it consumed less water. At the same time, increasing the area of forestland and grassland could weaken peak floods, and the water retention function of vegetation could prevent runoff from increasing and decreasing steeply. Therefore, it is worth improving vegetation coverage. HIGHLIGHTS Constructing 25 climate change scenarios based on CMIP5 simulation results and local temporal and spatial variation characteristics.; Constructing 4 land-use scenarios based on its variation characteristics and local development plan.; Simulating and quantifying runoff response to different climate and land-use change scenarios.; Identifying the major impact factors for runoff variability.; Experiment in the karstic basin, where there is a lack of related research.;